One-Dimensional Simulation of the Combustion Process in an Engine Cylinder with Ethanol - Akasyah, M Khathri; R., Mamat; Amir, Aziz; Azri, Alias; Nik Rosli, Abdullah (Trans Tech Publications Inc., 2014)
The diesel engine is one of the most important engines for road vehicles. The engine nowadays operates with different kinds of alternative fuels, such as natural gas and biofuel. The aim of this article is to study the combustion process that occurs in an engine cylinder of a diesel engine when using biofuel. The one-dimensional numerical analysis using GT-Power software is used to simulate the commercial four-cylinder diesel engine. The engine operated at high engine load and speed. The ethanol fuel used in the simulation is derived from the conventional ethanol fuel properties. The analysis of simulations includes the cylinder pressure, combustion temperature and rate of heat release. The simulation results show that in-cylinder pressure and temperature for ethanol is higher than for diesel at any engine speed. However, the mass fraction of ethanol burned is similar to that of diesel. MFB only affects the engine speed.